Effectiveness of Oral Bupropion and Nortriptyline as an Adjunct Treatment for Reducing the Use of Smokeless Tobacco: A Retrospective Study from a Tobacco Cessation Clinic in a Tertiary Care Hospital in Eastern India - Aparajita Guin; Hoineiting Rebecca Haokip; Sanjib Bandyopadhyay; Saibal Das; Indranil Saha; Aniruddha Basu; Stuti Bhargava (Indian Journal of Public Health)
Background: There is supporting evidence on the use of nortriptyline in smoking; however, its effectiveness in smokeless tobacco cessation has not been studied. Objectives: The objectives of this study were to evaluate the effectiveness of oral bupropion and nortriptyline in reducing smokeless tobacco use. Materials and Methods: In this retrospective study, 85 smokeless tobacco users who required pharmacotherapy (either bupropion or nortriptyline) in addition to behavioral counseling and standard nicotine replacement therapy were included in the study. The amount of tobacco use and Fagerström test for nicotine dependence (FTND)-smokeless tobacco score were compared at the end of 3 months of treatment. Results: Among 84 patients (92.9% males); 39 (46.4%) received bupropion and 45 (53.6%) received nortriptyline. Of them, 97.4% of patients who received bupropion and 84.4% who received nortriptyline reported reduced usage of smokeless tobacco after treatment (P = 0.06). There was a significant reduction in the average use of smokeless tobacco after treatment as compared to baseline usage among patients who received bupropion (median [Q1–Q3], 360 [150–600] to 8 [0–60]) and nortriptyline (median [Q1–Q3], 90 [0–465] to 0 [0–60]). Similarly, there were significant reductions in the median FTND-smokeless tobacco scores after treatment as compared to baseline scorings among patients who received bupropion (median, 6 [4–7] to 0 [0–0.5]) and nortriptyline (median, 6 [4–8] to 0 [0–0.25]). Both bupropion and nortriptyline were found to be safe. Conclusion: Adjunct bupropion and nortriptyline were similarly efficacious in reducing smokeless tobacco use. This has clinical significance because nortriptyline is much cheaper than bupropion.